[Jökulsá á Fjöllum Glacial Stream] - Streng, Evelyn Fiedler (1975)
Photograph of the Jökulsá á Fjöllum stream. The grey, rippled river winds through a grey stone platform. The jagged, canyon like stone platforms stretch across the photograph. A person with brown hair, a yellow shirt, and jeans stands to the right, looking down at the water. A mountain range is visible in the background to the left.